Criteria for rapid adaptability in judo during the training phase of athletes’ preparation - Rudenko, G.V.; Tkachuk, M.G.; Zaytsev, A.V.; Savelev, D.S. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify criteria for rapid trainability in judo athletes during the training phase of their preparation. Methods and structure of the study. A questionnaire survey was conducted to determine the level of fitness, physical fitness testing was carried out, anthropometric measurements were taken followed by the calculation of physical development indices, and blood group determination was performed. The study was conducted at the Olympic Reserve Sports School in the Vasileostrovsky District of St Petersburg. A total of 34 judo athletes aged between 12 and 14 years, representing all weight categories and with between 3 and 7 years’ experience in the sport, were examined. Results and conclusions. Analysis of the questionnaires revealed the individual timeframes within which judokas achieved a specific level of sporting qualification, enabling them to be divided into two groups: fast learners and slow learners. It was found that the morphological indicators reliably distinguishing fast-training judokas include: low values for the Yarkho-Kaupe weight-height index, the Pigne index and the proportionality index, a normostenic body type, and belonging to blood group III (B). Fast-training judokas outperform slow-training judokas in physical fitness according to the results of two tests: push-ups and forward bends from a standing position on a gymnastics bench. The data obtained can serve as criteria for the sporting selection of young judokas during the training phase.